2021
DOI: 10.1017/s2040174421000593
|View full text |Cite
|
Sign up to set email alerts
|

The significance of maternal asymptomatic bacteriuria during pregnancy on long-term offspring infectious hospitalizations

Abstract: Asymptomatic bacteriuria (ASB) is a well-acknowledged infectious entity during pregnancy; yet its long-term implications are not well investigated. The present study aimed to test the association between maternal ASB during pregnancy and long-term offspring infectious hospitalizations. A population-based cohort analysis was conducted, comparing the incidence of long-term infectious-related hospitalizations of offspring born to mothers who were diagnosed with ASB during pregnancy, and those who did not have ASB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Identifying gestational diabetes mellitus as a risk factor for maternal asymptomatic bacteriuria is important since it was associated with infectious disease of the offspring later in life. In a study that aimed to test the association between maternal asymptomatic bacteriuria during pregnancy and long term offspring infectious hospitalizations, it was found that asymptomatic bacteriuria during pregnancy increased offspring susceptibility to long-term infectious hospitalizations even after controlling for maternal age, diabetes mellitus, ethnicity, hypertensive disorders, and gestational age, thus, emphasizing the importance of screening high-risk populations for maternal asymptomatic bacteriuria, including women with gestational diabetes mellitus [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identifying gestational diabetes mellitus as a risk factor for maternal asymptomatic bacteriuria is important since it was associated with infectious disease of the offspring later in life. In a study that aimed to test the association between maternal asymptomatic bacteriuria during pregnancy and long term offspring infectious hospitalizations, it was found that asymptomatic bacteriuria during pregnancy increased offspring susceptibility to long-term infectious hospitalizations even after controlling for maternal age, diabetes mellitus, ethnicity, hypertensive disorders, and gestational age, thus, emphasizing the importance of screening high-risk populations for maternal asymptomatic bacteriuria, including women with gestational diabetes mellitus [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Долгосрочные последствия ББУ недостаточно изучены [33]. Был проведен популяционный когортный анализ, в ходе которого сравнивали частоту развития ИМП у потомства, рожденного от матерей, у которых во время беременности была диагностирована ББУ, и тех, у кого ББУ не было.…”
Section: Discussionunclassified
“…Проанализированы 212 984 истории родов. Среди всех беременных у 5378 (2,5%) была диагностирована ББУ; их дети чаще страдали ИМП [33]. Было установлено, что ИМП у беременной женщины представляет собой значительный фактор риска в отношении ИМП у ребенка: 30% против 6,8% [34].…”
Section: Discussionunclassified
“…Fetal programming is the hypothesis that describes the interaction between the offspring's long-term health and its in-utero environmental conditions [10]. Studies have associated maternal exposures during pregnancy such as smoking, maternal obesity, and maternal urinary tract infection with long-term infectious morbidity of the offspring [10][11][12][13]. FMF is known to cause a pro-in ammatory state that increases the secretion of IL-1, IL-18, and other mediators of in ammation that enhance chemotaxis and neutrophilia, inducing an FMF are [14].…”
Section: Introductionmentioning
confidence: 99%